(untitled) (Journal on studies and research of academic knowledge, 2008)
The Contingent Valuation Method has been applied to estimate the hypothetical willingness to paying an entrance fee to the Municipal Park Carlos Antonio Lopez, situated in the neighbourhood of Dr. Jose Gaspar Rodriguez de Francia, in the City of Asuncion, for imprvement of the premises and services. The undemaking of direct investigations taken place in situ during the month of September 2007 permited the characterization of the public who use the Park the uses they give it and the preference of activities which take place there. From the information collected it was found that 96% of the public interviewed were willing to pay the hypotheticall amount of G. 1.241,61 per visit.